UNA ESCALA DE VALORACION DE TERMINOS ASOCIADOS CON DISCAPACIDAD: PRIMEROS RESULTADOS - Aguado, Antonio León; Alcedo, María Angeles; Flórez, María Angeles (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
This research revolves around three main ideas. Firstly, the importance of attitudes of non disabled people faced with people with disabilities, a topic which has many assessment techniques and programs for a change of attitudes. Se condly, the importance of terminology associated with disability, a topic which lacks assessment resources. Thirdly, the relationship between terminology and attitudes, a problem which WHO attempted to solve with their proposal, the In ternational Classification of Impairments, Disabilities and Handicaps. In this context, this research aims to create a technique of assessment of attitudes through terms, using a twenty terms Likert scale, the Terms Associated with Disability Evaluation Scale (EVT), in order to analize the structure and ex tent of the terms’ semantic connotations, the relationship between terminology and attitudes towards disabled people, and their role in programs for modification, change and improvement of attitudes.